Improving English Language Class Learning Outcomes in Reading through the Implementation of Quizizz Application - Wahyuddin Wahyuddin; Sudarmanto Sudarmanto (Universitas Muhammadiyah Enrekang, 2023)
The utilization of technology in education involves the use of tools and technological applications to enhance the teaching and learning process. In this context, Quizizz serves as a relevant application that enables teachers to motivate students through various types of questions and good competitive elements. This includes measuring students’ comprehension, providing instant feedback, reinforcing material understanding, and monitoring students learning progress, resulting in improved learning outcomes. This research aims to determine the improvement of students learning outcomes in English language classes, especially in reading, by implementing the Quizizz application. The samples are used by students from the even semester of the academic year 2023/2024 in Muhammadiyah University of Parepare, focusing on second-semester students. The research uses the Classroom Action Research (CAR) method. Data was collected through tests and observations from June 2023 to July 2023. The results of this study indicate an improvement in learning outcomes, with an average learning outcome increase of 38% in cycle I and in cycle II by 78%.